The Corellation between Mother’s Knowledge and Attitude on Hypothermia in Preventing Hypothermia on Infant at Age 0 to 28 Days at Magersari Public Health Center Working Area, Magelang - Yana Listyawardhani; Farida Sukowati; Elisa Ulfiana (Journal of Health Science and Prevention, 2018)
Hypothermia became one of the primary cause on the high babies mortality in Indonesia, with the occurrence percentage reached 6.8%. Hypothermia which became the cause of death was directly related to the low-level knowledge and attitude in the 0 to 28 days infants treatment. The research aimed to investigated the relationship between the motherâ€™s knowledge on hypothermia with the their attitude in preventing hypothermia in infants at the ages 0 to 28 days Magersari Magelang Public Health Center working area. This is an observational analytic research with cross sectional design. Fifty-nine respondents acted as research sample and choosed with total sampling as a sampling technique and questionnaire as a research instrument. The Spearmanâ€™s Rank was used to analyzed the data. Respondents with a good knowledge about the hypothermia reached 32 peoples (68.2%) and 33 peoples (71.7%) have a positive attitude in the hypothermia prevention in infants with the ages 0 to 28 days. Spearman analysis generated 0.001 Ï value ( Ï < 0.05 ). The value of the correlation ( r ) reached 0.850, with the meaning there was a relationship between the mother knowledge of hypothermia with motherâ€™s attitude in hypothermia prevention in infants at the ages 0 to 28 days.